Differential retention and utilization of dissolved organic carbon by bacteria in river sediments - Helmut Fischer; Anke Sachse; Christian E. W. Steinberg; Martin Pusch (Limnology and Oceanography, 2002)
The differential ability of natural sediment biofilms to store and metabolize specific dissolved organic carbon (DOC) fractions was studied with a set of perfusion experiments that combined a chromatographic method for the analysis of several DOC fractions with the measurement of bacterial abundance and activity. High proportions of low‐molecular‐weight substances and polysaccharides and low but significant proportions of humic substances were retained in sediment cores after perfusion. Bacterial abundance and production in these cores were high (1.7—3.0 × 10 9 cells cm −3 and 0.7—12.0 µg C cm −3 h −1 , respectively). Bacterial abundance, production, and turnover times were correlated with the retention of various DOC fractions, especially polysaccharides, indicating a differential microbial utilization of DOC. Temperature as well as the quantity and quality of retained organic matter were the major factors that influenced bacterial production. However, particulate organic carbon represented the main energy source for sediment bacteria. It is concluded that certain fractions of DOC may be readily utilized for bacterial growth, irrespective of molecular size. Instead, the presence and abundance of specific chemical groups might be decisive. Hence, the processing of organic substrates by the microbial biofilm may largely influence the biogeochemistry of DOC in river waters.